My unexpectedly militant bots: A case for Programming-as-Social-Science. Issue 6 (November 2019) - Brooker, Phillip
This article examines bots – software applications that automate web-based tasks, and which often mimic human interaction and communication – to consider sociological responses to software design and computer programming. Leveraging design methodologies for critical sociological purposes (a) allows us to envision programming as a means of opening up 'black boxes' by engaging more directly with the code through which software applications are executed, and (b) indicates the potential for sociology practitioners to design software ourselves – to build applications that fulfil the radical promise of sociology by intervening in social processes. To concretise these ideas, this article presents two stories about social media bots developed by the author: 'Philbot' (a Facebook random status generator) and '@_Zen_Bot_ ' (a Twitter service that provides mock lifestyle advice to users). On the basis of this demonstration, the article proposes a near-future vision of sociology where Programming-as-Social-Science features as a core research method/skill/tool.